Eksplorasi Pengalaman Nasabah Dalam Penggunaan Mobile Banking Wondr By BNI (Studi Kasus Nasabah BNI KCP Jatimakmur Bekasi) - Andika, Putra; Krishantoro, Krishantoro (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This study aimed to explore customer experiences in using the wondr by BNI mobile banking application at the Jatimakmur Sub-Branch Office (KCP), Bekasi. A descriptive qualitative approach was employed, with data collected through in-depth interviews, observation, and documentation involving six informants, including BNI internal personnel, customers, and academics. The research focused on three customer satisfaction indicators as proposed by Tjiptono (2014): expectation confirmation, repeat usage, and recommendation to others. The findings indicated that most customers perceive the wondr by BNI application as meeting their expectations, particularly in terms of its modern interface, practical features, and transactional efficiency. Customers also demonstrated a tendency for continued use due to ease of access and system stability. However, some challenges were noted, such as technical issues and facial verification problems, which initially reduced satisfaction levels. Nonetheless, several customers still recommended the application to others. These findings suggested that service stability, feature clarity, and a positive initial experience are key factors in fostering customer satisfaction and loyalty toward mobile banking services